Are technological contributions in behavior guidance techniques superior to conventional methods?: Effects on dental anxiety and pain perception - Mücella Yazar; Sema Aydınoğlu; Dilara Nil Günaçar (BMC Oral Health)
Abstract Background To evaluate the effects of three different behavior guidance methods on children’s dental anxiety levels and pain perception. Methods This study included 63 children aged 6–8 years who required pulpotomy and were divided into three groups: tell–show–do (TSD; Group 1), TSD with video modeling (Group 2), and TSD with mobile phone application (Group 3). Systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and hemoglobin oxygen saturation (SPO2) of the participants were recorded before the procedure, after local anesthesia, after pulpotomy, and after the end of the procedure. Faces Version of the Modified Child Dental Anxiety (MCDASf), Wong-Baker Faces Pain Rating Scale (WBFPRS), and Face, Legs, Activity, Cry, Consolability (FLACC) pain scales were applied. Chi-squared test, one-way ANOVA, Kruskal–Wallis test, Friedman’s test, and repeated measurement analysis statistical tests were used. Results No significant difference was found between the steps in terms of BP, HR, and SPO2 within the groups (p > 0.05). When comparing the groups, there were significant differences in SBP (p = 0.040) and DBP (p = 0.027) measured at the beginning and end of the procedure, and between MCDASf (p = 0.041) and WBFPRS (p = 0.013) scores. These values ​​were lower in Group 3. Conclusion Dental anxiety and pain perception scores were lowest when using TSD with mobile phone application (Group 3). In line with developing technology, the use of mobile phone applications in pediatric dentistry can contribute to more harmonious treatment management in children. Trial registration The trial protocol was retrospectively registered ID NCT06912789 ( https://clinicaltrials.gov/ ); 2025-03-26.